2023
DOI: 10.1007/s10552-023-01668-0
|View full text |Cite
|
Sign up to set email alerts
|

Principles to operationalize equity in cancer research and health outcomes: lessons learned from the cancer prevention and control research network

Abstract: Reflecting their commitment to advancing health equity, the Cancer Prevention and Control Research Network (CPCRN) established a Health Equity Workgroup to identify and distill guiding principles rooted in health equity, community-engaged participatory research (CBPR), social determinants of health, and racial equity frameworks to guide its collective work. The Health Equity Workgroup utilized a multi-phase, participatory consensus-building approach to: (1) identify recurrent themes in health and racial equity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…While health and racial equity have been the cornerstone of many of its research efforts, the CPCRN, just recently, has explicitly operationalized a network-wide equity mission into its charter. Described by Chebli, et al [11], in response to the growing need to address equity, the CPCRN Health Equity Workgroup led a collaborative effort with CPCRN members to define a set of core health and racial equity principles that reflect and guide the ongoing and future research efforts of the network.…”
Section: Cancer Prevention and Control Research Network's Commitment ...mentioning
confidence: 99%
See 3 more Smart Citations
“…While health and racial equity have been the cornerstone of many of its research efforts, the CPCRN, just recently, has explicitly operationalized a network-wide equity mission into its charter. Described by Chebli, et al [11], in response to the growing need to address equity, the CPCRN Health Equity Workgroup led a collaborative effort with CPCRN members to define a set of core health and racial equity principles that reflect and guide the ongoing and future research efforts of the network.…”
Section: Cancer Prevention and Control Research Network's Commitment ...mentioning
confidence: 99%
“…As described in-depth elsewhere [11], this process was initially informed by a high-level review of the literature from which the preliminary equity principles were identified. When identifying the principles, it was of paramount importance to the Health Equity Workgroup to ensure robust participation from within the CPCRN in reviewing and vetting the principles.…”
Section: Cancer Prevention and Control Research Network's Commitment ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Three working groups are specifically focused on reducing health disparities and achieving health equity. The Health Equity Workgroup is developing resources for network members to aid in advancing health equity in cancer prevention and control [ 15 , 16 ]. These resources include: a set of guiding principles for health and racial equity; tools for measurement and evaluation of health and racial equity principles; and case studies to serve as examples of principles and guidance on how to implement them.…”
Section: Impact Of the Networkmentioning
confidence: 99%